Estudo do gengibre em pó e ácido lático como agentes modificadores do amido de milho - Silva, Ana Caroline da (2019)
The present work aimed to perform modification of corn starch using ginger powder and lactic acid, aiming application in bread of the type of form. Initially, the starch was modified with ginger powder in four different concentrations (5, 7, 9 and 11g / 100g of starch) and the best treatment for subsequent modification with lactic acid was also chosen in four concentrations (5, 10, 15 and 20%). Starches were studied for their structural and physicochemical properties. The optimized treatment and work was continued with the production of breads of form type control and added of modified starch in two concentrations (10 and 15%). The technological quality of the pasta and breads were studied, and the shelf life of the breads was evaluated by the determination of moisture and texture parameters during storage for 7 days. The statistical analysis of the data was done by analysis of normality, variance and regression, in addition to comparison of averages (Tukey) with a 5% significance level. The modification of corn starch using ginger powder promoted significant changes in the structure of the granules and reduction of its crystallinity. In addition, the rheological behavior of the starch was changed from Newtonian to dilatant and the viscosity was reduced. Starch with ginger showed less paste clarity, greater stability to the retrogradation process and less water exudation. The hydration properties of the granule were improved, and the pH was not altered. Starches modified with ginger and lactic acid showed greater changes in the surface of the granule and greater reduction of its crystallinity, besides the presence of constituents of the ginger in the starch even after the acid hydrolysis. The same rheological behavior was observed, however an increase in viscosity was observed. The clarity of paste was increased, as was the stability of the gels to retrograde at the initial stages of storage. The pH was reduced, reflecting in improvement in the hydration properties of the granule. The technological properties of the pasta and breads were improved by the addition of the modified starch with ginger and acid, resulting in loaves of larger volume and the color of these was altered by the incorporation of the starch. The study of the shelf life of stored loaves showed that the addition of modified starch decreased the loss of water, as well as delayed the hardening of the loaves and their loss of elasticity due to a delay in the process of retrogradation of the starch, thus improving its quality and increasing your shelf life.